Reducing Emissions from Deforestation and Forest Degradation (REDD+), Transnational Conservation and Access to Land in Jambi, Indonesia - Jonas Hein (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2013)
Indonesia is engaging in the UN-backed Reducing Emissions from Deforestation and Forest Degradation scheme (REDD+) to reduce its land-use-based greenhouse gas emissions. This paper begins with the assumption that REDD+ and general trends towards privatization of nature and conservation are impacting the ability of local communities to access land. Drawing on fieldwork conducted in Jambi in 2012, I explore land access patterns in the context of Indonesia's emerging REDD governance framework. Initial findings show that, despite recent REDD-related forest governance reforms, land tenure issues remain unresolved. The results of fieldwork in the Harapan Rainforest area show that the reality on the ground is still characterized by overlapping and competing land claims backed by different authorities.
urn:nbn:de:gbv:7-webdoc-3904-5
Keywords: 330; REDD; land tenure; forest governance; conservation; Indonesia